STRATEGY TO IMPROVE THE CONVENIENCE QUALITY OF STREET VENDOR AREAS IN BANDUNG CITY - Hapsoro, Nur Arief; Fauziah, Ghorizatunnisa Al; Azaria, Nadine Anela; Damayanti, Tasya Rizqi; Balqis, Tiara (Universitas Telkom, 2023)
The city of Bandung is one of the culinary tourism destinations, including culinary fromstreet vendors. Street vendors are often visited by the people of Bandung or outside the city. Unfortunately, thereare still some street vendors that are inadequate for visitors. This is caused by a lack of attention tothefunctions and users of public open spaces where street vendors sell in general. The purpose of this study is todetermine the factors that can af ect the convenience of street vendors so that in the future it is hoped that thestreet vendors area in Bandung can meet the needs of the community. This study uses a quantitative methodby distributing questionnaires and taking data from 107 respondents online which then the results of the dataare analysed for correlation between studies and also using the multivariate regression method. The resultsobtained indicate that the factors that can af ect the convenience level of street vendors are the easeof access to visit street vendors and the ease of access to parking is the most powerful factor influencingtheconvenience of visiting. The benefit of research for the author is that it increases knowledge, and canbeaconsideration for policy makers and regional designers when designing street vendor areas. Keywords : Regression; Street vendor; Visiting convenience.